STUDENTS’ IMPROVING VOCABULARY BY DISCORD AS AN ALTERNATIVE ASYNCRHONOUS LEARNING MEDIA - Bintang Fedora Aditya; Anita Dewi Ekawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
Since Discord was released to the public in May 2015, gamers have widely used it as an additional team talk application to communicate with their teammates while playing games. However, this program is also utilized as an alternate communication media in English teaching and learning activities because it has a lot of capabilities. Consequently, the purpose of this study is to ascertain how students feel about utilizing Discord as a learning tool to broaden their vocabulary during asynchronous learning. This study uses a descriptive quantitative research method. This research consisted of 125 senior high school students from two schools in South Jakarta. Data collection uses a Google Form which is distributed through classes and several class groups. The results of these data are that the use of Discord as an alternative asynchronous learning media can improve vocabulary acceptable because it supports the features of their language use in the application. With this in mind, the use of Discord continues to this day as an alternative learning media for students.